2022
DOI: 10.1007/978-3-030-89412-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Female Agri-Food Start-Ups: Mapping the Italian Context During the Coronavirus Era

Abstract: This is the official book series of SIDREA -the Italian Society of Accounting and Business Administration. This book series is provided with a wide Scientific Committee composed of Academics by SIDREA. It publishes contributions (monographs, edited volumes and proceedings) as a result of the double blind review process by the SIDREA's thematic research groups, operating at the national and international levels. Particularly, the series aims to disseminate specialized findings on several topicsclassical and cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…However, as the multiple case study has confirmed, the trigger for new knowledge comes from the relationships the company has established with the external environment and thus the RC's composition. This implication theorized in the paper is also evident from the fact that the role of RC is observed in a sector that is currently very deficient in terms of innovation, namely agri-food (Modaffari and Manzo, 2023; Paoloni et al. , 2022a; Cosentino et al.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 69%
See 4 more Smart Citations
“…However, as the multiple case study has confirmed, the trigger for new knowledge comes from the relationships the company has established with the external environment and thus the RC's composition. This implication theorized in the paper is also evident from the fact that the role of RC is observed in a sector that is currently very deficient in terms of innovation, namely agri-food (Modaffari and Manzo, 2023; Paoloni et al. , 2022a; Cosentino et al.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 69%
“…In 2022, women only led ten innovative agri-food start-ups. Namely, 11% of the agri-food sector and only 0.08% of the innovative Italian start-ups (Modaffari and Della Corte, 2021; Modaffari and Manzo, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations